Cultural gender schemes vs. emotional parameters of men and women functioning in professional athletics - Mroczkowska, H. (Biology of Sport, 2005)
The aim of presented work was the determination of influence of the "male" cultural patterns on the emotional parameters of athletes functioning. Groups of women (n=64) and men (n=78) fencers and judokas were examined. Their age amounted to x ~18 and sport experience to x ~6 years. In the sphere of psychological gender two groups of women and two of men were isolated: with high and low cultural "male" psychical pattern. The following questionnaire measurement techniques were adapted: Psychological Gender Inventory PGI determining the "male" gender profile; Self-esteem questionnaire STAI as for the fear factor as a state (Fs) and as a trait (Ft) measurement; Personality Inventory as for the neuroticism recording (N); Temperamental Questionnaire FCZ-KT for the recording of perseveration and stress resistance. Despite of the stated relationship of the psychological gender and psychophysical emotional costs there are no grounds for assumption that the cultural gender matrix levels differences between women and men. Women with strongly developed "male" psychic model turn to be closer in behaviour to men with the opposite, weak psychological matrix. When women and men with similar psychological patterns are compared the emotional costs of women are higher. De facto, the relationship of emotional costs and psychological gender is present only in the sphere of the same biological sex. The lack of developed "male" psychic is undoubtedly connected with the increased emotional costs. On the other hand, having the "male" psychological model does not guarantee the emotional functioning of women on the same level which display men with related psychological matrix.